Upaya Meningkatkan Kemampuan Berhitung Permulaan Melalui Bermain Stick Angka Pada Anak Kelompok B Di TK Desa Wonolopo Tasikmadu Karanganyar Tahun Ajaran 2015/2016 - MULYANINGSIH, YENIS ASTINA (2016)
ABSTRACT Yenis Astina Mulyaningsih/A520110011. THE EFFORT TO INCREASE THE FIRST COUNTING ABILITY THROUGH STICK FIGURES PLAYING TOWARD B GROUP CHILDREN IN KINDERGARTEN WONOLOPO VILLAGE TASIKMADU KARANGANYAR IN THE ACADEMIC YEAR OF 2014 - 2015. Research Paper. Education and Teacher Faculty, University of Muhammadiyah Surakarta,January, 2016. Caunting is a good way to promote a lifelong learning. Based on Doman, best time for studying caunting is together with the time when the child learn to speak, and the sensitivity of learning occurs in the age of 3 to 5. The use of simple play activities at children is the cause of the low first caunting ability. Stick figures playing is an alternative to increase the ability of first caunting ability at children on the earlier age. The purpose of this research is to increase the first caunting ability through stick figures playing toward b group children in Wonolopo Village kindergarten school. This kind of research paper is classroom action research with two cycle work procedure, consist four steps. The subject are teacher and children in group B in Wonolopo Village Tasikmadu Karanganyar. This result shows that the stick figures playing is able to increase the first caunting ability. The percentage from pre action class room research to cycle II is, pre cycle 47.25%, cycle I 57.75% and cycle III 86.37%. The conclusion of this research is that stick figures playing is able to raise the first caunting ability in kindergarten Wonolopo Village in the academic year of 2014 - 2015.